1992
DOI: 10.1254/jjp.60.307
|View full text |Cite
|
Sign up to set email alerts
|

Kangenkaryu Prevents the Decrease of Cholinergic Markers Following the Nucleus Basalis Magnocellularis Lesion.

Abstract: ABSTRACT-The nucleus basalis magnocellularis (nbm)-lesioned rat is considered to be a model of the cholinergic dysfunction observed in the cerebral cortices of Alzheimer's disease patients. The cholin ergic markers, acetylcholine release and choline acetyltransferase activity, were decreased in the cerebral cortex of the nbm-lesioned rat. Kangenkaryu (KAN), a Chinese traditional medicine, is a typical prescription for the treatment of symptoms related to blood circulation deficiency. Orally ad ministered KAN f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 10 publications
0
24
0
Order By: Relevance
“…This extract is used to treat symptoms related to blood circulation deficiencies and is well known to reduce blood and plasma viscosity and thereby improve microcirculation (11). Pharmacological evidence demonstrates that KK exhibits biological activities such as platelet aggregation inhibition (12), hypertension suppression (13), and anti-hyperlipidemia (14).…”
Section: Introductionmentioning
confidence: 99%
“…This extract is used to treat symptoms related to blood circulation deficiencies and is well known to reduce blood and plasma viscosity and thereby improve microcirculation (11). Pharmacological evidence demonstrates that KK exhibits biological activities such as platelet aggregation inhibition (12), hypertension suppression (13), and anti-hyperlipidemia (14).…”
Section: Introductionmentioning
confidence: 99%
“…4) However, the pharmacological mechanisms of KGK in improving microcirculation had not been studied. In the present study, we discuss the anti-thrombotic effect of KGK by evaluating its in vivo effects on the coagulation system and platelet-aggregative activity.…”
mentioning
confidence: 99%
“…A previous clinical report showed that KGK improved hypertension, arteriosclerosis, headache and dizziness (Tanaka, 1993), and animal experiments have demonstrated that KGK prolonged the tail-bleeding time, inhibited platelet aggregation in mice (Makino et al, 2002) and suppressed hypertension in spontaneously hypertensive rats (Gao et al, 2001). KGK also recovered the learning and memory impairment in senescence accelerated mouse by preserving the activities of choline acetyltransferase and superoxide dismutase in the cerebellum (Takahashi et al, 1992).…”
Section: Introductionmentioning
confidence: 83%